Physiological Effects of Some Artificial and Natural Food Coloring on Young Male Albino Rats - Dafallah, Abdellah A; Abdellah, Abdelmonem M; Abdel-Rahim, Emam A; Ahmed, Sherif H (Journal of Food Technology Research, 2015)
Food colorants are widely added to food in order to attract the consumer. Recent researches have incriminated these additives for causing some problems to human health. This study was conducted to determinate the physiological effects of some natural (curcumin, carrotin and curcumin) and synthetic (tetrazine, sunset yellow and erythosine) food colorants on some hematological and biochemical parameters of male albino rats (rattus norvegicus, spraguedawlay strain). Results revealed that administration of synthetic food colorants decreased the percentage of high density lipoprotein cholesterol (HDL-C), glutathione secretion (GSH), superoxide dismutase (SoD), and plasma immune-system and significantly increased plasma lipid lipoprotein, total cholesterol (LDL-C), lipid peroxidase, blood glucose, plasma urea and creatinine and increased activities of alkaline phosphatase, acid phosphatase, and lactate dehydrogenase. Hence, it is recommended to avoid adding synthetic colorants as additive to foodstuff, while natural colorants seemed to be the best choice as food colorants.